Integrative “omic” analysis reveals distinctive cold responses in leaves and roots of strawberry, Fragaria × ananassa ‘Korona’ - Koehler, Gage; Rohloff, Jens; Wilson, Robert C.; Kopka, Joachim; Erban, Alexander; Winge, Per; Bones, Atle M.; Davik, Jahn; Alsheikh, Muath K.; Randall, Stephen K. (Frontiers in Plant Science, 2015)
To assess underlying metabolic processes and regulatory mechanisms during cold exposure of strawberry, integrative “omic” approaches were applied to Fragaria × ananassa Duch. ‘Korona’. Both root and leaf tissues were examined for responses to the cold acclimation processes. Levels of metabolites, proteins, and transcripts in tissues from plants grown at 18°C were compared to those following 1 to 10 days of cold (2°C) exposure. Overall, ‘Korona’ showed a modest increase of protective metabolites such as amino acids (aspartic acid, leucine, isoleucine, and valine), pentoses, phosphorylated and non-phosphorylated hexoses, and distinct compounds of the raffinose pathway (galactinol and raffinose). By 2DE proteomics a total of 845 spots were observed in leaves; 4.6% changed significantly in response to cold.Transcript levels in leaves were determined by microarray, where dozens of cold associated transcripts were quantitatively characterized, and levels of several potential key contributors (e.g., the dehydrin COR47 and GADb) to cold tolerance were confirmed by qRT-PCR. Cold responses are placed within the existing knowledge base of low temperature stress change in plants, allowing an evaluation of the uniqueness or generality of Fragaria responses in photosynthetic tissues. Overall, the cold response characteristics of ‘Korona’ are consistent with a moderately cold tolerant plant.